COMMUNITY EMPOWERMENT THROUGH CREATIVE ECONOMY ENTERPRISES IN CREATING TOURISM VILLAGES - Nabella, Mayfa; Rahmadanita, Annisa (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2024)
The problem in Melikan Village in running the pottery business is that the pottery-making process still uses manual tools, and the raw materials used are difficult to obtain. The study aimed to obtain an overview of community empowerment through Creative Economic Enterprises in realizing a tourist village in Melikan Village. The researcher chose Melikan Village from 5 Pottery Tourism Villages in Wedi Subdistrict as a research project because Melikan Village still maintains its ancestors' heritage in making pottery using manual techniques. In addition, the form of pottery made is only based on the ideas and creativity of each craftsman. This research employed a qualitative method with a descriptive approach. Data collection techniques were conducted through interviews, observation, and documentation. The results show that the government holds training socialization by bringing in the Industry Office, which is held twice a month to develop the creativity of the craftsmen. In addition, in terms of budget, the craftsmen only rely on personal budgets, not the local governments. Supporting factors include the potential for self-taught creativity of the craftsmen, enthusiasm, and positive response from the community. Meanwhile, the inhibiting factor factors are the competition between craftsmen in determining the selling price of pottery to consumers. In addition, the craftsmen also complained about the raw materials used to make pottery, which are now difficult to obtain in their villages. Hence, they have to take them from neighboring villages. In conclusion, community empowerment through creative economic businesses in developing tourist villages in Melikan Village is categorized as good enough. Keywords: Tourism Village, Community Empowerment, Creative Economy Business.